2013
DOI: 10.1371/journal.pntd.0001982
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Ehrlichia canis in Dogs in Malaysia

Abstract: An epidemiological study of Ehrlichia canis infection in dogs in Peninsular Malaysia was carried out using molecular detection techniques. A total of 500 canine blood samples were collected from veterinary clinics and dog shelters. Molecular screening by polymerase chain reaction (PCR) was performed using genus-specific primers followed by PCR using E. canis species-specific primers. Ten out of 500 dogs were positive for E. canis. A phylogenetic analysis of the E. canis Malaysia strain showed that it was group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 21 publications
2
27
1
1
Order By: Relevance
“…The detection of E. canis DNA in 22.9% of the sampled population of dogs was higher than the prevalence of 12.7% reported by Kamani et al (2013) in the northern part of Nigeria and those reported by Nazari et al (2013) and Lasta et al (2013) in Malaysia and Brazil, respectively. The higher occurrence reported in this study may partly be associated with the predominance of the tick vector (Rhipicephalus sanguineus) of the parasite in the study area (Oke et al, 2013) and may be due to optimum environmental conditions that favour its breeding.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The detection of E. canis DNA in 22.9% of the sampled population of dogs was higher than the prevalence of 12.7% reported by Kamani et al (2013) in the northern part of Nigeria and those reported by Nazari et al (2013) and Lasta et al (2013) in Malaysia and Brazil, respectively. The higher occurrence reported in this study may partly be associated with the predominance of the tick vector (Rhipicephalus sanguineus) of the parasite in the study area (Oke et al, 2013) and may be due to optimum environmental conditions that favour its breeding.…”
Section: Discussioncontrasting
confidence: 63%
“…The prevalence and molecular characteristics of Ehrlichia canis have been studied extensively around the world (Suksawat et al, 2001;Unver et al, 2001;Vinasco et al, 2007;Aguiar et al, 2008;Harrus et al, 2011;Nazari et al, 2013;Milanjeet et al, 2014;Cardoso et al, 2016). One of these studies has revealed that more than one strain may exist in a region (Vinasco et al, 2007).…”
mentioning
confidence: 99%
“…canis has been detected and reported in dogs from many parts of the world Rani et al 2011;Sasaki et al 2012;Ybañez et al 2012;Nazari et al 2013;Aktas et al 2015;Inpankaew et al 2016). An analysis of our results revealed a 28% overall prevalence of E. canis (N = 42) in the studied blood samples from the three districts, suggesting that E. canis is prevalent in Punjab province (Table 1) but the prevalence of E. canis varied significantly between three sampling areas indicating that geographical features and climatic conditions do affect the parasite prevalence (Rani et al 2011;Mircean et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in countries situated in and around the Middle Eastreport the presence of vector-borne pathogens including Anaplasma platys, Ehrlichia canis, Bartonella spp.,and Babesia spp. in dogs and cats [9,13,14,15,16,17,18,19].Currently, limited studies have examined the presence of vector-borne disease in dogs and cats in Saudi Arabia [7,20,21,22,23]. Therefore, the aim of this study was to evaluate the presence of vector-borne pathogens in dogs and cats in two different climatic zones of Saudi Arabia using a commercial diagnostic MT-PCR panel for the detection of Babesia gibsoni, Babesia vogeli, Mycoplasma haematoparvum, Mycoplasma haemocanis, Mycoplasma haemofelis, Anaplasma platys and Bartonella species.…”
Section: Introductionmentioning
confidence: 99%